If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 7xb Solving 12 = 7bx Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7bx' to each side of the equation. 12 + -7bx = 7bx + -7bx Combine like terms: 7bx + -7bx = 0 12 + -7bx = 0 Add '-12' to each side of the equation. 12 + -12 + -7bx = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -7bx = 0 + -12 -7bx = 0 + -12 Combine like terms: 0 + -12 = -12 -7bx = -12 Divide each side by '-7x'. b = 1.714285714x-1 Simplifying b = 1.714285714x-1
| 5x-36=-3x+20 | | 125a^3+15a-27b^3-9b= | | ln(2)+ln(x)=1 | | 6x-23=2x+13 | | 2(5+m)=-2(1-7m) | | 8+9=115 | | -7-3x=13-5x | | 3x-4=-3+2x | | -40+6x=37-5x | | .5x+3=1.5x | | .08=.05c-7.50 | | 2x-5+4x+9=6x-25+4x-2 | | 3.05x=8.6 | | X^3+11x^2-x+17=0 | | 2a+5=9a-9 | | 7g^2+14g=0 | | 28=-7k | | 9x+12x-15=0 | | 3*(2.5*x)=6.6 | | 3x-49=86-6x | | 3y-1-2y=16 | | 3x-10+2x=65 | | 15r+3(3-r)=1 | | 3y-1=16 | | 20-16x+4-36=0 | | 2(f+57)+30=178 | | 2(x-3)+5+x=3 | | 6x+2=-4x | | 4(y+5)+4=44 | | 4*7+-13= | | f(x)=3(x-2)(x+5) | | 19-5x=7-7x |